Design and Implementation of a Compact Automated Spirulina Cultivation System for Households - Esmaeili, Seyed Ebrahim; AlRasheedi, Ahmed; AlJarrah, Ahmed; Marzouk, Mohamed H; AlBloushi, Fatmah Y (Indonesian Journal of Agricultural Research, 2023)
Spirulina is considered to be the most nutritious whole food source in nature. It is promoted as a dietary supplement and an active ingredient in functional foods. Factors such as conflicts, supply chain disruptions, and economic fallout are driving food prices to unprecedented levels. Low- and middle-income populations are affected by these rising costs. The design and implementation of a compact Spirulina cultivation system to be used in the household is presented in this paper. The system contains light, temperature, pH, and turbidity sensors. All sensors are connected to microcontrollers which activate a heater, air pump, mixing pump, pool fall pump, and two LEDs according to the readings received to ensure proper and continuous growth of Spirulina. The proposed system is user-friendly, economical, and can be easily stored and operated at homes to stimulate and monitor the growth of Spirulina. The primary objective of the proposed compact cultivation system is to furnish the necessary tools for generating a nutritionally valuable food source on a smaller scale, specifically within households, at a relatively affordable cost.